RECONSTRUCTING AND MODELLING LATE WEICHSELIAN CLIMATES: THE YOUNGER DRYAS IN EUROPE AS A CASE STUDY - Isarin R.F.B.; Renssen H. (My University, 1999)
The science of climatology has evolved rapidly during the last few decades due to the growing awareness that global climate is likely to change. Research has been focused on understanding climate change and on assessing the effects of these changes on man and its environment. To understand climate change it is crucial to look at climatic variations in the geological past. Former climates (or palaeoclimates) may be reconstructed by inferring climatic information from geological and ecological, so-called proxy, data. Also, palaeoclimates may be simulated with global climate models, so-called atmospheric general circulation models (AGCMs). Comparison of reconstructions with these simulations improves our understanding of the mechanisms behind the studied palaeoclimate. Here, we review progress that has been made in this important field of research. We focus on climate reconstructions using the multi-proxy approach in which different kind of proxy data are analysed to obtain a wide range of climate parameter values. Moreover, the process of comparison with climate models is thoroughly examined. Furthermore, we illustrate aspects of climate reconstruction and modelling with a study on the Younger Dryas (YD) climate in Europe.